Nursing care of a patient after pericardiocentesis in terms of the International Classification of Nursing Practice ICNP® – a case study - Filip M. Tkaczyk (Problemy Pielęgniarstwa)
Pericardiocentesis is an invasive procedure to evacuate accumulated fluid in the pericardial sac by puncturing and decompressing it. Pathological accumulation of fluid in the pericardial cavity is an immediate life-threatening condition and may be the cause of sudden cardiac arrest. The aim of this study is to present the nursing process of a patient after pericardiocentesis using the terminology of the International Classification of Nursing Practice ICNP®. The study used the case study method and the technique of interviewing, observing, measuring, and analysing the patient’s medical records. The study was conducted in January 2024 and included a 51-year-old man hospitalised for angioplasty with complications of cardiac tamponade. The most important nursing problems were taken into account in the patient’s nursing process. The risk of complications of fluid accumulation in the pericardial sac was reduced, and vital parameters were normalised.